2007
DOI: 10.1111/j.1742-6723.2006.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience in adverse events detection in an emergency department: Incidence and outcome of events

Abstract: In conclusion, the Quality in Australian Health Care Study methodology has been utilized to provide data on incidents and AE in an ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 43 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…One article was identified in the hand search. A total of ten publications, representing eight studies (two studies reported results in two publications each [20], [21], [22], [23]) were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One article was identified in the hand search. A total of ten publications, representing eight studies (two studies reported results in two publications each [20], [21], [22], [23]) were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The included articles (Table 2 and Table S3) were prospective, observational studies: seven prospective cohort studies [9], [10], [20], [21], [24], [25], [26], [27] and one before-and-after interventional design [22], [23], [27]. Methodological quality was low to moderate with weaknesses in study group comparability, follow-up, and outcome ascertainment and reporting (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are defi ned as unintended injuries or complications caused by health care management, rather than by the patient's underlying disease and that lead to death, disability at the time of discharge or prolonged hospital stay [2]. While, 35 to 70% of AEs have been judged to be preventable [3][4][5], they appear to be responsible for 44,000 to 98,000 accidental deaths and over one million excess injuries each year [6,7]. The situation is thought to be more challenging in developing countries with higher risk of patient harm due to the limitation of resources and lack of adequate infrastructures [8].…”
Section: Introductionmentioning
confidence: 99%
“…The rest of the events occurred during the ED visit. Drug reactions and diagnostic issues were the most common types of events 11 12…”
Section: Discussionmentioning
confidence: 99%